Personnel adjustments during the Covid-19 pandemic: Did co-determination make a difference? - Daniel Fackler; Claus Schnabel; Jens Stegmaier (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2021)
Using a unique dataset of establishments in Germany surveyed during the Covid-19 pandemic, this study investigates whether personnel adjustments during the crisis differed between establishments with and without a works council. Our regression analyses show that the hiring and dismissal rate as well as the churning rate were lower in establishments with a works council. In contrast, the net employment growth rate over the pandemic and the implementation of short-time work did not differ significantly between establishments with and without a works council. We conclude that worker co-determination did indeed make a difference in terms of higher employment stability for the incumbent workforce during the pandemic. – – Anhand einer Befragung von Betrieben in Deutschland während der Covid-19-Pandemie untersucht diese Studie, ob sich die Personalanpassungen während der Krise zwischen Betrieben mit und ohne Betriebsrat unterschieden. Unsere Regressionsanalysen zeigen, dass die Einstellungs- und Entlassungsraten wie auch die Churning-Rate in Betrieben mit Betriebsrat geringer ausfielen. Dagegen unterschieden sich die Netto-Wachstumsrate der Beschäftigung und die Inanspruchnahme von Kurzarbeit nicht signifikant zwischen Betrieben mit und ohne Betriebsrat. Wir schlussfolgern, dass in der Pandemie Arbeitnehmermitbestimmung tatsächlich einen Unterschied für die Beschäftigungsstabilität der vorhandenen Mitarbeiter/-innen machte.
Keywords: J53; J63; M51; 330; works councils; co-determination; personnel adjustments; Covid-19 pandemic